PENYULUHAN NARKOBA DAN DAMPAKNYA TERHADAPPENINGKATAN PENGETAHUAN, SIKAP DAN PERILAKU PADASISWA SMK - Rahem, Abdul; Umi Athiyah; Wahyu Utami; I Nyoman Wijaya; Hanni Prihhastuti Puspitasari; Anila Impian Sukorini; Mufarrihah, Mufarrihah; Ana Yuda; Yuni Priyandani; Catur Dian Setiawan; Andi Hermansyah (Jurnal Bakti untuk Negeri, 2025)
Drug abuse among the younger generation is increasing over time and greatly affects the future life of the nation and the state. Factors that influence drug abuse include personality, family, economic conditions, environment, and social interactions, which at first often arise due to a lack of knowledge about the dangers of drugs. The effects of drug abuse include physical, psychological, social, and security impacts. Because misunderstanding or low levels of knowledge is one of the factors in drug abuse, counseling/health education is important to be carried out for the younger generation in Bojonegoro Regency, as one of the areas prone to drug abuse among high school students. Counseling was provided to 238 students of grades 10 and 11 at SMK Negeri Dender,Bojonegoro Regency. The success of the counseling was evaluated using pre-and post-tests. The evaluation results were statistically tested to determine differences before and after counseling in students’knowledge, attitudes, and behaviors related to drug abuse. The analysis showed p-values for knowledge=0.000,for attitude=0.044,and for behavior=0.000. All values were<0.05,which means that there were significant differences in knowledge, attitudes, and behaviors before and after the counseling. In conclusion, the counseling improved students’knowledge, attitudes, and behaviors regarding the dangers of drugs and their abuse.